Diskursus Yuridis Bukti Elektronik dalam Perkara Perceraian: Analisis Komparatif Dua Putusan Pengadilan Agama - Ardelia Fairuz , Numara (Universitas Jambi, Fakultas Hukum, 2025)
This study examines the use of electronic evidence in divorce proceedings at Religious Courts, focusing on the differences in judicial reasoning. The divergence is evident in the decision of the Gedong Tataan Religious Court No. 0371/Pdt.G/2020/PA.Gdt, which rejected electronic evidence for not meeting formal requirements, compared with the Tulang Bawang Religious Court decision No. 0501/Pdt.G/2017/PA.Tlb, which accepted such evidence despite its lack of formal validity. The research gap lies in the inconsistency of applying the provisions on electronic evidence after the enactment of the Electronic Information and Transactions Law (ITE Law), which creates potential legal uncertainty. This study employs a normative juridical method with statutory, case, and conceptual approaches. Its contribution is to provide an understanding of the legal basis and judicial practice in assessing electronic evidence in divorce cases, as well as how judges interpret the principle of authenticity. The findings reveal that the Gedong Tataan judges emphasized formal aspects and excluded electronic evidence even when undisputed, while the Tulang Bawang judges applied the presumption of authenticity by accepting undisputed evidence. This contrast highlights the need for clearer standards to ensure legal certainty in the use of electronic evidence in divorce cases.